PENGARUH MINAT, LINGKUNGAN DAN PENDAPATAN TERHADAP PERMINTAAN PRODUK BRAND WAKWOK (STUDI KASUS MAHASISWA DIKAMPUS NEGERI KOTA MEDAN) - Farhan Lubis; Muhammad Arif; Juliana Nasution (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
This study aims to determine the Effect of Interest, Environment and Income on Demand for Brand Wakwok Products (Case Study of Students at Medan City State Campus). This study uses quantitative methods and associative approaches, data collection techniques using questionnaires and population and samples in this study were 67 students from 4 state campuses in Medan City, namely: USU, UNIMED, UINSU, and POLMED. The data were analyzed using multiple linear regression methods. The results of this study indicate that Interest (X1) affects the Demand for Brand "WakWok" Products, Environment (X2) affects the Demand for Brand "WakWok" Products, Income (X3) affects the Demand for Brand "WakWok" Products, and Interest, Environment¸ and Income simultaneously affect the Demand for Brand "WakWok" Products. This can be seen that the variation in the variables of Interest, Environment, and Income is able to explain the variation in the Demand for Brand "WakWok" Products variable by 53.5%.